Chemokines in Cancer Development and Progression and Their Potential as Targeting Molecules for Cancer Treatment - Naofumi Mukaida; So-ichiro Sasaki; Tomohisa Baba (Mediators of Inflammation)
Chemokines were initially identified as bioactive substances, which control the trafficking of inflammatory cells including granulocytes and monocytes/macrophages. Moreover, chemokines have profound impacts on other types of cells associated with inflammatory responses, such as endothelial cells and fibroblasts. These observations would implicate chemokines as master regulators in various inflammatory responses. Subsequent studies have further revealed that chemokines can regulate the movement of a wide variety of immune cells including lymphocytes, natural killer cells, and dendritic cells in both physiological and pathological conditions. These features endow chemokines with crucial roles in immune responses. Furthermore, increasing evidence points to the vital effects of several chemokines on the proliferative and invasive properties of cancer cells. It is widely acknowledged that cancer develops and progresses to invade and metastasize in continuous interaction with noncancerous cells present in cancer tissues, such as macrophages, lymphocytes, fibroblasts, and endothelial cells. The capacity of chemokines to regulate both cancerous and noncancerous cells highlights their crucial roles in cancer development and progression. Here, we will discuss the roles of chemokines in carcinogenesis and the possibility of chemokine targeting therapy for the treatment of cancer.